2014
DOI: 10.1183/09031936.00069714
|View full text |Cite
|
Sign up to set email alerts
|

Serum 25-hydroxyvitamin D levels and lung function in adults with asthma: the HUNT Study

Abstract: The association between vitamin D status and lung function in adults with asthma remains unclear.We studied this cross-sectional association and possible modification by sex and allergic rhinitis in 760 adults (aged 19-55 years) with self-reported asthma in the Nord-Trøndelag Health Study. Serum 25-hydroxyvitamin D (25(OH)D) level <50 nmol·L −1 was considered deficient. Lung function measurements included forced expiratory volume in 1 s (FEV1) % predicted, forced vital capacity (FVC) % predicted and FEV1/FVC r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 32 publications
(36 reference statements)
1
18
0
Order By: Relevance
“…16 However findings of this study were consistent with HUNT study that concluded that low serum 25(OH)D level was not associated with airway obstruction in most asthma adults. 17 The current study showed lack of seasonal variation in vitamin D levels which were consistent with a study from Iran. 18 However many other studies reported seasonal variation with an increase in value in the summer season.…”
Section: Discussionsupporting
confidence: 92%
“…16 However findings of this study were consistent with HUNT study that concluded that low serum 25(OH)D level was not associated with airway obstruction in most asthma adults. 17 The current study showed lack of seasonal variation in vitamin D levels which were consistent with a study from Iran. 18 However many other studies reported seasonal variation with an increase in value in the summer season.…”
Section: Discussionsupporting
confidence: 92%
“…Serum 25(OH)D levels were categorised based on the most recent Institute of Medicine report (<50 or ⩾50 nmol·L −1 ) [11], or used as a continuous independent variable. As previously described [12], spirometry was performed by trained health professionals at screening stations. Instrument quality control was conducted once daily via staff lung function assessment.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, instead of measuring cord serum 25(OH)D, both KOALA and Canadian studies determined the level of 25(OH)D during preschool or school age. Regarding to the relationship between 25(OH)D and lung function in adults, the HUNT study revealed that low serum 25(OH)D level was not associated with airway obstruction in most asthma adults with the exception of males with asthma but without allergic rhinitis [36]. Therefore, drawing conclusions about the effects of perinatal and postnatal vitamin D status from these results can be difficult.…”
Section: Discussionmentioning
confidence: 99%